Pengaruh Edukasi Tentang Diare Dengan Menggunakan Media Leaflet Terhadap Tingkat Pengetahuan Ibu Dalam Pencegahan Diare Pada Balita Di Puskesmas Wonoasih Kota Probolinggo - Pratiwi, Maharani Puti (Jurnal Keperawatan Muhammadiyah, 2021)
Background : Diarrhea is the frequency of defecating more than 3 times a day within 24 hours with a liquid consistency. Diarrhea disease is still one of the important public health problems because it is the main contributor to the three morbidity and mortality rates for children after pneumonia in various countries, especially in developing countries, one of the developing countries is Indonesia. Goals : The purpose of this study was to know the effect of education on the level of mother’s knowledge in preventing of diarrhea in children at Wonoasih Public Health Center, Probolinggo City. Research methods : The design of this study uses Quasy-Experimental with a pretest-posttest with Control Group approach. Data were collected using a questionnaire with a total sample of 30 intervention groups and 30 control groups using a total sampling technique. Results : The results of the analysis that have been carried out using the wilcoxon test showed differences in the level of knowledge before and after in the intervention and control groups showed a significant value 0,001 (p<0,05) Ha accepted means that there is an effect of education about diarrhea using leaflet media on the level of mother’s knowledge in preventing of diarrhea in children at Wonoasih Public Health Center, Probolinggo City. Conclusion : There is the influence of the before and after is done to knowledge education mother. Keywords : Diarrhea, Education, Knowledge